Sistem Rekomendasi Event Online Menggunakan Metode Content Based Filtering - Fahmi Nurfalah; Asriyanik; Agung Pambudi (STEKOM PRESS, 2022)
Covid-19 has spread widely with various variants, disrupting human social activities, the activities in question include the implementation of events, but there are other alternatives by utilizing technology, events can still be held online. However, the number of events that are held online makes it difficult for someone to find the event they want because there are too many events on the website so someone experiences information overload. Therefore, the authors conduct research with the goal to make it easier for someone to find the event they want by implementing a recommendation system on the website. In this study, the authors make a recommendation system using the Content-Based Filtering method in recommending an online event. The results of this study obtained an accuracy of 86% of the performance of the model carried out by SVM.